Szlifowanie Powierzchni Płaskich za Pomocą Tarcz Ściernych - A. Ripianu; C. Tudosie (Engineering Transactions, 1963)
A cylindrical abrasive disc is considered in the process of grinding a plane surface by means of its end surface constituting a circular ring. The abrasive disc rotates about its geometric axis which is fixed in general. The ground object performs a rectilinear or rotatory motion about axis parallel to the axis of the disc. The disc performs also direction if the ground surface forms a translational motion, in the vertical a recess. Three diffesent cases are considered.